A simplified piecewise-hyperbolic softening model of skin friction for axially loaded piles. (April 2019) - Xu, Ling-Yu; Shao, Wang-Da; Xue, Ying-Ying; Cai, Fei; Li, Yong-Yi
Abstract: In this study, a simplified piecewise-hyperbolic softening (SPS) model is proposed to characterize both softening and hardening behaviors of skin friction. A highly effective finite element program is developed for the nonlinear analysis of axially loaded piles. The applicability of the proposed method is verified by an analytical solution and two well-documented filed tests of axially loaded piles. Moreover, a parametric study is conducted to investigate the influence of various parameters of the SPS model on the load-settlement relationship of piles. Finally, the results obtained from the SPS model are compared with those obtained from other two existing softening models.